1999
DOI: 10.1002/(sici)1096-9918(199908)27:8<735::aid-sia567>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of polypropylene/(ethylene–propylene) copolymer blends (PP/EP): application to injection‐moulded systems

Abstract: Polypropylene/ethylene-propylene copolymer blends (PP/EP) were characterized by time-of-flight (ToF). SIMS, by dynamic wetting and by atomic force microscopy and force modulation spectroscopy (AFM-FMM).In a first step, model systems of compression-moulded PP/EP physical blends were prepared. With these materials, ToF-SIMS provides linear relationships between the selected peak and the EP content in the material. This indicates that both phases are present at the surface in the same concentrations as in the bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…SIMS characterizations of random copolymers have already been reported in the literature, but extracting relevant information on the unit contents, often based on the empirical selection of characteristic peaks, proved to be a difficult task. Peaks have to be selected with extreme care. A study on poly(styrene- r -butadiene) showed for instance that intensity ratios of selected peaks can exhibit linear or nonlinear relationships with respect to the comonomer content .…”
Section: Introductionmentioning
confidence: 99%
“…SIMS characterizations of random copolymers have already been reported in the literature, but extracting relevant information on the unit contents, often based on the empirical selection of characteristic peaks, proved to be a difficult task. Peaks have to be selected with extreme care. A study on poly(styrene- r -butadiene) showed for instance that intensity ratios of selected peaks can exhibit linear or nonlinear relationships with respect to the comonomer content .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple strategies were used for selecting ToF-SIMS peaks to be included in the data matrix. Initially, peaks were selected on the basis of reference libraries and previous assignment in the literature for polypropylene and surface treated polypropylene . Peaks were also assigned by using the library and the exact mass calculator tool in the Ionspec software (Ion-TOF GmbH, Germany) to identify contaminant peaks, the hydrocarbon peaks, and peaks that were likely to correspond to fragments of the flame treatment that were not listed in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Pressure p was determined by the type of nozzle installed at the end of the water pipe. Different vapor jet test conditions are specified for the automobile industry 6. The following conditions were used in this study: T = 60°C, t = 60 s, d = 100 mm, α = 90°, p = 68 bar, and nozzle type = 2506.…”
Section: Methodsmentioning
confidence: 99%
“…It does not contain rubber particles 4, 5. Tomasetti et al6 characterized the surface composition of PP/EPR blends: surface phase segregation should lead to the presence of mainly pure PP in the first 100 nm of the surface, but this PP skin should not be completely closed. The role of EPR in the formation of the skin layer is still speculative.…”
Section: Introductionmentioning
confidence: 99%